The Behavior of Opening and Closing Prices Noise and Overreaction - Sumiyana, Sumiyana (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2009)
This study extends several previous studies that conclude that noise and overreaction on intraday data occur. Those studies have yet to be clear about the kind of price that explains for this noise and overreaction. This study examines the opening price and closing price behavior, and tries to explain the noise and overreaction on the Indonesia Stock Exchange using intraday data in every 30-minute interval. Sample is firms listed in LQ45 index. Sequentially, this research sample is filtered to stocks that are the most actively traded on the Indonesia Stock Exchange based on trading frequency in an observation period from January to December 2006. This research finds that noise and overreaction phenomena always occur in the opening and closing prices. In addition, investors actually correct the noise and overreaction that occur simultaneously at the first 30-minute interval on every trading day.